The Utilization of Artificial Intelligence Technology in the Transformation of Smart and Environmentally Friendly Office Management - Anwar, Raka Saipal; Trio Ramadhan (Asosiasi Ahli Administrasi Indonesia, 2026)
The development of Artificial Intelligence (AI) has driven significant changes in modern office management. The implementation of AI enhances operational efficiency through automated workflows, algorithm-based data analytics, and the optimization of energy usage and facility management. However, conventional office management practices still face challenges, including inefficiencies, high energy consumption, and limited adoption of environmental sustainability principles. This study aims to analyze the role of AI in supporting the transformation toward environmentally friendly smart offices through its integration with the Internet of Things (IoT) and Green Human Resource Management (GHRM) practices. This research employs a literature review method based on recent scholarly sources. Findings indicate that AI has the potential to reduce carbon footprints, improve workplace environmental quality, and strengthen sustainability-oriented organizational culture. Nevertheless, successful implementation of AI requires adequate infrastructure readiness, enhanced human resource competencies, and robust governance of data privacy and security. With appropriate strategic planning, AI can serve as a catalyst for developing efficient and sustainable office management systems.